Perubahan Osmolaritas Pasien Hiperglikemia Dengan Terapi Rehidrasi - lutfi, erik irham (Holistic Nursing and Health Science, 2019)
AbstractIntroduction Disease patterns change in the World led to significant increases of non infectious diseases, one of which is DM hyperglycemia with Indonesian rank fifth in the World. Uncontrolled DM hyperglycemia will lead an increase in osmolarity that will disrupt the body's fluid and electrolyte balance. The primary management of hyperglycaemia according to ADA is by fluid rehydration therapy. Rehydration therapy will replace the body fluid composition caused by hyperosmolarity. Successful replacement of rehydration fluids can be seen by monitoring continuous and sustained hemodynamics and osmolarity. This study aims is to analyze the changes of  osmolarity hyperglycemia patients with receiving rehydration therapy.Metods : This study included into comparative studies with a cohort approach. The number of samples in this study as many as 56 respondents. Date collection using consecutive sampling technique.Result :  From the result of the research based on the bivariate analysis test, there are different of osmolarity before and after rehydration therapy (p value 0,000).Discussion : Rehydration therapy giving decreased of hiperosmolarity in hyperglicemia patients. Continuous checking  osmolarity needed for hyperglycemic patients receiving rehydration therapy to determine the effect of rehydration therapy and to know the side effects of rehydration therapy so that prevention can be done to avoid problems causing emergency situations.